Identifying NPF Genes Involved in Arbuscular Mycorrhizal Symbiosis - Gariano, Daniel (Université d'Ottawa / University of Ottawa, 2022)
Arbuscular mycorrhizal (AM) fungi are a group of fungi that are able to establish a symbiotic relationship with the root system of many land plants. This symbiosis improves plant fitness by increasing the uptake of crucial mineral nutrients, particularly phosphorus and nitrogen. In return, the fungi receive organic carbon from the plant host in the form of sugars and lipids. The objective of my research is to assess whether the Nitrate and Peptide Transporter Family (NPF) of transport proteins play a role in mediating AM symbiosis. Firstly, we explored the involvement of NPF genes NPF1B and NPF4.12 by examining the phenotype of Medicago truncatula mutants. Secondly, we employed a modified yeast two-hybrid system to determine the phytohormone import capabilities of these NPF transport systems. Lastly, we employed reporter gene fusions to assess the spatial and temporal expression profiles of these NPF genes. The results of our research do not support our hypothesis that these NPF genes play a role in mediating AMF symbiosis. The results of the modified yeast-two hybrid tests revealed abscisic acid (ABA) and gibberellic acid (GA3) import capabilities of the transport system encoded by the gene NPF4.12. Future study of the diverse mechanisms that underpin AM symbiosis will nonetheless be useful to the agricultural industry by reducing farmer's reliance on chemical fertilizers.
Keywords: NPF; Arbuscular Mycorrhizal Fungi; Medicago truncatula